EFFECT OF DIETARY SUPPLEMENTATION OF PROTECTED FATS ON POST DILUTION INTERVAL AND SEMEN QUALITY OF BEETAL BUCKS (The Research of Medical Science Review, 2024)
Artificial insemination (AI) made a great contribution to the development of the livestock industry but deleterious effects of cryo-preservation on sperm fertility are profound. Effects of dietary supplementation of rumen protected fats on the semen quality in Beetal bucks were evaluated. Sperm quality of fresh and diluted semen was assessed through dietary supplementation of protected fats in Beetal bucks. A total of 20 Beetal bucks having nearly similar age (1.5 year) and weight (22 kgs) were selected, divided into five groups having four animals each in a completely randomized design. One group was controlled and the rest of the groups were supplemented with protected fats at the rate 10, 20, 30 and 40 gm per kg dry matter intake (DMI). The Collected semen was diluted in Tris-Glucose-Citrate-Yolk extender. The sperm quality parameters like sperm volume, sperm motility, sperm concentration and individual motility were determined at intervals of 0, 1, 2, 24, and 96 hours in fresh and diluted semen. There were no significant (p>0.05) effect on the semen volume, concentration, mass motility and individual motility at different intervals. It is concluded from the present study that the supplementation of protected fats has no significant effect on fresh semen whereas protected fat supplementation up to 30 gm per kg DMI preserved individual motility of semen that is an indicator for quality of Beetal buck semen